(untitled) (World Bulletin of Public Health, 2024)
It was established that pharmacotherapy of pregnant women was carried out in 100% of cases; during the gestation period, an average of 12.6 drugs were prescribed. The greatest number of drugs was used simultaneously in the second trimester (an average of 5.5); in the first and third trimesters this number was an average of 2.4 and 4.7, respectively. In the structure of prescriptions, the leaders were vitamin and mineral complexes (70.4%), agents for local vaginal sanitation (37.1%), gestagens (33.1%), herbal uroseptics (29.8%), systemic antibiotics (14.2%). Defects in pharmacotherapy included: prescription of drugs that do not correspond to the diagnosis - 48.6% of cases, a combination of several drugs with the same pharmacological action - 16.5%, polypharmacy - simultaneous prescription of 5 or more drugs - 25.8%.